Purification, characterization, gene cloning, and sequencing of a new beta-glucosidase from Bacillus circulans subsp. alkalophilus. - Paavilainen, S (1993)
An intracellular beta-glucosidase was purified from cell extracts of Bacillus circulans subsp. alkalophilus by NAD affinity and high-performance anion-exchange chromatographies. The enzyme was active against a wide range of aryl-beta-glucosides and beta-linked disaccharides. The structural gene for beta-glucosidase was cloned in Escherichia coli. The beta-glucosidase gene consisted of an open reading frame of 1,350 bp encoding a protein of 450 amino acids with a calculated M(r) of 51,303. The enzyme exhibited from 45 to 66% identity with five bacterial beta-glucosidases.